ASPEK HUKUM KEBEBASAN BERPENDAPAT DALAM MEDIA SOSIAL DAN PERLINDUNGAN HUKUM MASYARAKAT ATAS BERITA BOHONG - Hadi Karyono; Dwinanda Linchia Levi Heningdyah Nikolas (PSHPM Untag Semarang, 2025)
In the Indonesian constitutional system, one of the manifestations of democracy and popular sovereignty is the freedom of opinion and expression guaranteed by the 1945 Constitution, freedom of opinion and expression is a human right (Article 28). This right is regulated by international law and national law. However, the fact is that the implementation of freedom of opinion and expression in social media causes a lot and does not pay attention to human rights and the legal interests of others. In this research, the research approach used is normative juridical using secender data as the main data (primary legal materials, secender legal materials, tertiary legal materials) supported by primary data (observations and interviews), the research data is analyzed descriptively qualitative. The results showed (1) Freedom of opinion and expression in social media in Indonesia in the form of digital platforms such as social media has many misunderstandings in its implementation (2) The implementation of freedom of opinion in social media in Indonesia must be limited by the responsibility to maintain ethics, not harm others, and conflict with applicable laws in Indonesia.